2016
DOI: 10.3390/ijms17050630
|View full text |Cite
|
Sign up to set email alerts
|

PNPLA3 Expression Is Related to Liver Steatosis in Morbidly Obese Women with Non-Alcoholic Fatty Liver Disease

Abstract: Recent reports suggest a role for the Patatin-like phospholipase domain-containing protein 3 (PNPLA3) in the pathology of non-alcoholic fatty liver disease (NAFLD). Lipid deposition in the liver seems to be a critical process in the pathogenesis of NAFLD. The aim of the present work was to evaluate the association between the liver PNPLA3 expression, key genes of lipid metabolism, and the presence of NAFLD in morbidly obese women. We used real-time polymerase chain reaction (PCR) analysis to analyze the hepati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
13
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(14 citation statements)
references
References 57 publications
1
13
0
Order By: Relevance
“…Circulating PCSK9 has also been found to be significantly associated with hepatic expression of SREBP‐1c and FASN, whereas PCSK9 mRNA levels have been found to be significantly correlated with steatosis severity and hepatic APOB, SREBP‐1c, and FASN expression (Ruscica et al , ). Aragones et al () have evaluated the association between liver PNPLA3 expression, key genes in lipid metabolism, and the presence of NAFLD in morbidly obese women and have reported that PNPLA3 expression was related to HS in these subjects. Their analysis indicates that PNPLA3 may be related to lipid accumulation in the liver, mainly in the development and progression of simple steatosis.…”
Section: Discussionmentioning
confidence: 99%
“…Circulating PCSK9 has also been found to be significantly associated with hepatic expression of SREBP‐1c and FASN, whereas PCSK9 mRNA levels have been found to be significantly correlated with steatosis severity and hepatic APOB, SREBP‐1c, and FASN expression (Ruscica et al , ). Aragones et al () have evaluated the association between liver PNPLA3 expression, key genes in lipid metabolism, and the presence of NAFLD in morbidly obese women and have reported that PNPLA3 expression was related to HS in these subjects. Their analysis indicates that PNPLA3 may be related to lipid accumulation in the liver, mainly in the development and progression of simple steatosis.…”
Section: Discussionmentioning
confidence: 99%
“…Despite the emergence of PNPLA3 associated genetic risk for hepatic diseases, only few studies have investigated the pathophysiological regulation of PNPLA3. In a recent study by Aragones et al 32 increased PNPLA3 expression was associated with NAFLD. In contrast with this study, we did not observe a correlation between liver injury or weight loss on However, I148M-associated NAFLD is not associated with insulin resistance or adipose tissue inflammation.…”
Section: Discussionmentioning
confidence: 86%
“…Despite the emergence of PNPLA3 associated genetic risk for hepatic diseases, only few studies have investigated the pathophysiological regulation of PNPLA3 . In a recent study by Aragones et al . increased PNPLA3 expression was associated with NAFLD.…”
Section: Discussionmentioning
confidence: 86%
“…It has been shown that steatoshepatosis and hepatic fibrosis never develop in PNPLA3 knockout mice, and in conditions of gene hyperexpression, the synthesis of triglycerides and their accumulation in the carriers of the G-allele increases in connection with the genetically determined lower hydrolytic activity of the adiponutrin enzyme (17). The presence or appearance of obesity also affects the growth of the accumulation of triglycerides in carriers of the G-allele (18). Some authors point out that liver damage at non-alcoholic fatty dystrophy and ALD is diverse in nature, they differ in the phenotype of the disease and, accordingly, varying degrees of its progression (19).…”
Section: Study Resultsmentioning
confidence: 99%